Identificação molecular , sensibilidade a fungicidas e reação de cultivares de soja a Cercospora spp. e Diaporthe spp. - Silva, Monikéli Aparecida da (2025)
This study aimed to: 1) identify species of Cercospora spp., Colletotrichum spp., and Diaporthe spp. from isolates collected in different Brazilian states; 2) investigate the phytopathogens associated with pod and grain rot (PGR) and stem breakage (SB) in soybean; and 3) evaluate the sensitivity to fungicides and the reaction of soybean cultivars to the fungi. In Chapter I, isolates of Cercospora and Colletotrichum were identified through molecular analysis. The species C. cf. flagellaris and C. sigesbeckiae, as well as cryptic species, were identified. For Colletotrichum, the identified species were C. plurivorum (46%), C. truncatum (42%), C. sojae (8%), and C. siamense (3%). In Chapter II, the sensitivity of Cercospora and Colletotrichum isolates to fungicides SDHI, QoI, DMI, and SBI was evaluated based on the effective concentration 50% (EC50), and the G143A mutation was analyzed in Cercospora. The Cercospora and Colletotrichum isolates showed insensitivity to QoI and SDHI fungicides; however, the Colletotrichum isolates were sensitive to BZF. The isolates showed higher sensitivity to DMI and SBI fungicides. The G143A mutation was detected in 86% of the Cercospora isolates. In Chapter III, the reaction of soybean cultivars inoculated with Cercospora and Colletotrichum was evaluated. The cultivar BMX Desafio RR was the most susceptible to CFC and anthracnose, while NEO610 IPRO showed the highest resistance, and BMX Lança IPRO was intermediate. The isolates UPFCe09, UPFCe18, UPFColl02, UPFColl04, and UPFColl12 exhibited the highest aggressiveness. In Chapter IV, the incidence and molecular identification of fungi in soybean samples with PGR and SB symptoms were evaluated. The fungi Diaporthe, Colletotrichum, Macrophomina, and Cercospora were the most frequent in soybean samples. The species D. longicolla, D. ueckeri, and D. masirevicii were identified through molecular analysis. Koch's postulate showed that Diaporthe, Colletotrichum, and Macrophomina can cause PGR symptoms. Regarding the reaction of soybean cultivars to Diaporthe, BMX Desafio presented the least disease severity, while NEO610 exhibited intermediate severity, and CZ48B32 and BMX Lança showed the highest severities. The Diaporthe species were moderately sensitive to insensitive to the SDHI fungicide and sensitive to the QoI, DMI, and SBI fungicides.